Gastrointestinal myiasis by Eristalis tenax in Costa Rica - Rivera Barquero, Ángelo (2015)
Gastrointestinal myiasis infestations are rare and difficult to identify because of its inespecific symptoms and requirement of defecate the larvae to make an accurate diagnosis. The first reported case of gastrointestinal myiasis Eristalis tenax in Costa Rica is presented. The patient is a 45 year old woman who lives in a rural area with problems of drinking water. She presents chronic diarrhea, abdominal pain, and foreign body sensation in the anus and casual expulsion of Eristalis tenax larvae as identified in her feces This record extends the registration of cases of human myiasis gastrointestinal Eristalis tenax in America to 09° 50'55 "N, the most northern case in America.